Plant genomics and agriculture: from model crops to other crops, the role of data mining for gene discovery - Mahalakshmi, V.; Ortíz, R. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2001)
Sequencing and analysing of the Arabidopsis thaliana genome, the first plant kingdom genome to be unraveled, will always remain a scientific landmark. International initiatives to sequence rice, the most important cereal in Asia, are underway. However as functional information piles up in Arabidopsis and rice, researchers working in other crops will benefit from this new knowledge and apply it to their studied plants or crop species. The increasing role of public databases of model organisms and bio-informatics in data mining, presents a new opportunity as well as a challenge to researchers to develop more focused molecular tools for gene discovery and deployment. The work presented in here describes how such an approach has benefited sorghum, a rainfed semi-arid troprical cereal.